Tacrolimus intrapatient variability and rejection are associated with inferior allograft outcomes after kidney transplantation - Javed, Maryam; Sanghera, Aruna; Khan, Azhar Ali; Nagpal, Ria; Butler, Katie; Hobill, Abigail; Gage, Alice; Karst, Felix; Needleman, Amy; Hmun, Mya; Thal, Nicola; Shirling, Graham; et al. (Frontiers in Nephrology, 2025)
IntroductionEarly kidney transplant failure has significant negative impact for individuals and healthcare systems. Contemporary data investigating early allograft failure are lacking. We undertook a retrospective observational cohort study of adult patients who underwent kidney transplantation at a single European centre.MethodsWe determined causes of allograft failure between 1 and 5 years after transplant and explored clinical variables present at 1 year that predicted allograft loss.Results591 patients (median age 50 years, 64.1% male, and 44% white) were included; 531 (89.8%) had graft survival and 60 (10.2%) had graft loss between 1- and 5-years. Rejection was the primary cause of graft failure in 24 (40%) cases and 54% had undetectable tacrolimus levels prior to failure event. Female sex, serum creatinine at 1 year, the occurrence of rejection, and undetectable tacrolimus levels were associated with increased odds of graft loss. In subsequent analysis of 787 patients alive with a functioning graft at 1 year, recipient age, serum creatinine, proteinuria, any rejection episode, and tacrolimus intrapatient variability (IPV) at 1 yearwere associated with an increased hazard of graft loss.DiscussionHence, graft losses were predominantly alloimmune mediated, often associated with non-adherence, and were predicted by tacrolimus IPV at 1 year.